Multimodal discourse analysis of Uruguayan ecoinfluencers on Instagram - Garzón Díaz, Carolina (2023)
This article presents a multimodal discourse analysis of Uruguayan ecoinfluencers active in one of the most popular social networks in the region from the environmental communication perspective, it attempts to determine which environmentalisms are important in the public digital conversation. Moreover, it analyzes the environmental discourse of a sample consisting of 200 Instagram posts from 17 influencers, created between June 2021 and June 2022. The environmental challenges and their possible responses are predominantly located in the individual lifestyle sphere, with consumers as protagonists, and ecoefficiency is considered as the environmentalism that best synthesizes the attitudes and proposed actions. Pollution is the environmental crisis most frequently addressed in these discourses, compared to the limited presence of climate change, and the informative or educational topics are those prevailing in the publications.